A Handbook for Gram Panchayats : To Help Them Plan, Implement, Operate, Maintain and Manage Drinking Water Security - World Bank (Washington, DC, 2014)
The Department of Drinking Water Supply (DDWS), Ministry of Rural Development, Government of India launched the National Rural Drinking Water Program (NRDWP) on 1st April, 2009. The NRDWP builds on experiences gained through past efforts by many stakeholders and brings all existing rural drinking water initiatives under a single program. The focus of the NRDWP is to ensure drinking water security for all rural citizens in India. Drinking water security means providing every rural person with enough safe water for drinking, cooking and other domestic needs at all times and in all situations, including periods of drought and flood and for livestock. The Gram Panchayats (GP), as leaders and representatives of the community, has to take the lead in achieving this goal of drinking water security. The Gram Panchayats, through Village Water and Sanitation Committees (VWSCs), have to mobilize communities, educate them and ensure they get the necessary training and technical support to achieve drinking water security. The gram Sabha is the main platform for taking decisions and approving plans. The handbook seeks to serve as a quick reference for GP and VWSC on how to plan, implement, operate, maintain and manage water supplies and to ensure their sustainability. The handbook is based on the NRDWP guidelines. The focus of this handbook is to ensure 'drinking water security' in rural India.